Real-Time Simulation of a Curtailment Service Provider for Demand Response Participation - Abrishambaf, Omid (2021)
The daily increment of the electricity use, obligates the network operators to utilize the new concepts, such as demand response programs. These programs have a minimum capacity in the consumption reduction, therefore, the small and medium consumers cannot participate in such programs individually. Curtailment Service Provider is a new concept that can overcome this barrier, by aggregating the small and medium consumers. However, testing and validating the concepts of Curtailment Service Provider with real data in realistic scenarios is required before the massive implementation of the business models. Therefore, this paper represents a real-time simulation of a Curtailment Service Provider including 220 consumers, and 68 distributed generations. In the case studies, the reactions of two small and medium prosumers are surveyed based on different decisions of Curtailment Service Provider.